2019
DOI: 10.14499/indonesianjpharm30iss2pp122-127
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thionamide to TRH, TSH, IL-4, T-REG, and Anti-TPO in Graves’ Disease

Abstract: The most common cause of hyperthyroidism is Graves' disease. TRH and TSH are hormonal factors that modulate and control thyroid function in Graves' disease. In the immunological aspect, Graves' disease is played by the role of T-reg, IL-4, and anti-TPO. Graves' disease treatment goal is to inhibit thyroid hormone secretion by administering thionamide. The evaluation of this treatment is its hormonal and immunological aspects. To describe the effect of thionamide on serum TRH, TSH, IL-4, T-reg, and anti-TPO lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The TRH effect is initiated by binding of peptides with G protein-coupled receptor (GPCR) on the thyrotropic plasma membrane. TRH secretion is influenced by thyroid hormones through a negative feedback mechanism in the hypothalamic-pituitary-thyroid axis [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TRH effect is initiated by binding of peptides with G protein-coupled receptor (GPCR) on the thyrotropic plasma membrane. TRH secretion is influenced by thyroid hormones through a negative feedback mechanism in the hypothalamic-pituitary-thyroid axis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Measuring anti-TPO can be used as a predictive marker in diagnosing patients with autoimmune thyroid disorders. [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…These genes control immune responses such as major histocompatibility complex genes, T cell receptor genes, and antibody genes and genes that encode autoantigen targets in autoimmune thyroid disease. Recent studies have found that promoter gene polymorphisms are associated with Graves' disease [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of Graves' disease worldwide is estimated as much as 0.4% of cases per year and is more experienced by women in the ratio of 5:1 [2,3]. In Indonesia, 0.4% of Indonesia's population aged 15 years or older has hyperthyroidism [4,5].…”
Section: Introductionmentioning
confidence: 99%